The Shelf Life Estimation of Cold Sterilized Coconut Water - Kailaku, Sari Intan; Setiawan, Budi; Sulaeman, Ahmad (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2017)
Coconut water is well known due to its nutrient contents. Unfortunately, the properties such as flavor, aroma, and taste is easily altered, soon after it is extracted from the fruit by splitting the fruit in two and collecting the water in a clean container. The shelf-life of coconut water drink can be improved by eliminating the enzyme that causes the degredation of the quality, i.e. polyphenol oxidase and peroxidase enzyme. Heat treatment such as pasteurization and Ultra Heat Treatment may inhibit the growth of these enzymes although resulted in the loss of coconut water unique and desirable properties. Ultrafiltration membrane and ultraviolet are two potential cold-sterilization methods. The objective of this research was to estimate the shelf-life of coconut water after ultrafiltration membrane and ultraviolet sterilization. Cold-sterilized coconut water was stored at three temperatures, i.e. 8, 13 and 25 °C, using polyethylene bottles in individual sizes (250 ml). The shelf-life was estimated using Accelerated Storage Study method with Arrhenius equation. pH and total sugar contents were measured as critical parameters, and total plate count was also observed. This research concludee that the shelf-life of coconut water which cold sterilized without any food additives was etimated to be 15 days at 25 °C.